Founding 49ers : The Dark Days before the Dynasty - Newhouse, Dave, 1938- (Book collections on Project MUSE., 2015)
The San Francisco 49ers are among the most dynamic franchises, not only in the National Football League but in all of professional sports. They have won five Super Bowl titles and have produced some of football's most dynamic players in Joe Montana, Jerry Rice, and Ronnie Lott, all of whom were coached by Bill Walsh, one of the game's most innovative thinkers. The 49ers' greatness came 35 years after the franchise began in 1946. During those years, they achieved no conference or league titles, even though they produced eight Pro Football Hall of Fame inductees, including the celebrated "Millio.